2018
DOI: 10.1002/cncr.31406
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatocellular carcinoma by age, sex, and liver disorder status: A prospective cohort study in Korea

Abstract: With advancing age, the effects of alcohol use and HCV on the development of HCC become stronger, whereas the effect of male sex weakens. Lifetime moderate alcohol consumption may cause HCC in the elderly. Smoking increases the risk of HCC irrespective of viral hepatitis, and diabetes increases the risk of HCC independent of cirrhosis. Cancer 2018;124:2748-2757. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 32 publications
4
58
1
Order By: Relevance
“…The evidence for protection given by moderate alcohol intake on NAFLD has however been challenged ( Table 2) [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. In the Italian Dionysos study, a study exploring the prevalence of liver disease in the general population of two Italian towns [49], alcohol use was associated with both fatty liver incidence and remission when graded for any 20 g/day in both men and women.…”
Section: Moderate Alcohol Consumption and The Liver Within And Outsidmentioning
confidence: 99%
“…The evidence for protection given by moderate alcohol intake on NAFLD has however been challenged ( Table 2) [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. In the Italian Dionysos study, a study exploring the prevalence of liver disease in the general population of two Italian towns [49], alcohol use was associated with both fatty liver incidence and remission when graded for any 20 g/day in both men and women.…”
Section: Moderate Alcohol Consumption and The Liver Within And Outsidmentioning
confidence: 99%
“…Alternatively, the reduced prevalence of advanced fibrosis among women versus men may be due to a lower frequency of cofactors for liver disease progression, such as alcohol use. (13)(14)(15)…”
Section: Natural History Of Hcv Among Womenmentioning
confidence: 99%
“…That is one of the motivations for our study. 1 For example, to our knowledge, evidence has been lacking regarding whether smoking increases the risk of HCC independent of HBV and HCV infection, or in the HBV-negative and HCV-negative populations. 2 Our study included all traditional risk factors with the exception of aflatoxin.…”
Section: Reply To Risk Factors For Hepatocellular Carcinomamentioning
confidence: 99%
“…An article written by Yi et al recently published in Cancer reported that current smoking was associated with an increased risk of developing hepatocellular carcinoma irrespective of viral hepatitis (hazard ratio, 1.26; 95% confidence interval, 1.15-1.38). 1 Currently, major risk factors for hepatocellular carcinoma worldwide are chronic hepatitis B infection, chronic hepatitis C infection, diabetes mellitus, heavy alcohol consumption, nonalcoholic fatty liver disease, and aflatoxin. [2][3][4][5][6] Without these traditional risk factors, the risk of developing hepatocellular carcinoma is relatively low.…”
mentioning
confidence: 99%